2020
DOI: 10.1111/ap.12468
|View full text |Cite
|
Sign up to set email alerts
|

The origin, experimental basis, and application of the standard interview method: An information‐gathering framework

Abstract: The standard interview method (SIM) is a guidance framework for information gathering interviews. This article describes the purpose, scope, origin, experimental basis, and practical application of the SIM. It provides an informative overview of developments to date for psychologists and researchers within the behavioural sciences, as well as for practitioners who might use the SIM. The SIM contains core evidence-based components but is otherwise open to tailoring and modifications to suit a variety of intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 78 publications
0
29
0
1
Order By: Relevance
“…Powell and Brubacher (2020) emphasize that “practice examples need to be developmentally and culturally appropriate so that all children can complete them successfully” (p. 6). Children’s apparent difficulty with the IDU instruction in Danby and colleagues’ study led Powell and Brubacher (2020) to warn interviewers against the metacognitive challenges of signaling incomprehension, and to recommend that interviewers only introduce one instruction per interview, preferably the don’t know instruction. Our results suggest that an alternative approach would be to utilize the IDU instruction and to accept less than explicit references to incomprehension as appropriate responses.…”
Section: Discussionmentioning
confidence: 99%
“…Powell and Brubacher (2020) emphasize that “practice examples need to be developmentally and culturally appropriate so that all children can complete them successfully” (p. 6). Children’s apparent difficulty with the IDU instruction in Danby and colleagues’ study led Powell and Brubacher (2020) to warn interviewers against the metacognitive challenges of signaling incomprehension, and to recommend that interviewers only introduce one instruction per interview, preferably the don’t know instruction. Our results suggest that an alternative approach would be to utilize the IDU instruction and to accept less than explicit references to incomprehension as appropriate responses.…”
Section: Discussionmentioning
confidence: 99%
“…The Standard Interview Method (SIM) is a protocol framework developed to accommodate these adaptations (Powell & Brubacher, 2020). A new SIM is created in every new partner relationship in which we work.…”
Section: Commentary 10 Horse Before the Cart: Solid Foundations Support Informed Adaptationmentioning
confidence: 99%
“…A guide for investigative interviewers to use in evaluating their peers may be a necessary but not sufficient tool. Interviewers would have to be sufficiently skilled interviewers themselves to accurately evaluate performance (Lamb et al , 2018; Powell, 2013; Powell and Brubacher, 2020). A study with 50 nursing students in Thailand showed that peer ratings using an assessment scale were uncorrelated with ratings by experts using the same scale the first time it was used, but by the second assessment, ratings from students and experts were significantly related (Lai, 2016).…”
Section: Peer Review As a Mode Of Workplace Learningmentioning
confidence: 99%
“…Who is Lolo?” [After child’s response] “Tell me more about what happened in the tent with Lolo”). A non-exhaustive list of guidelines structured in this manner includes the National Institute of Child Health and Human Development protocol (Lamb et al , 2018); Tom Lyon’s 10 step version (Lyon, 2005); the National Children’s Advocacy Center’s (NCAC) Investigative Interview Structure (NCAC, 2019); Guidance for Achieving Best Evidence in Criminal Proceedings (Ministry of Justice, 2011) and the standard interview method (SIM; Powell and Brubacher, 2020).…”
Section: General Overview Of Best Practices In Interviewingmentioning
confidence: 99%
See 1 more Smart Citation